The Productivity Impact of Global Warming: Firm-Level Evidence for Europe - Nicola Gagliardi; Elena Grinza; François Rycx (Institute of Labor Economics (IZA), 2024)
We investigate the impact of rising temperatures on firm productivity using longitudinal firm-level balance-sheet data from private sector firms in 14 European countries, combined with detailed weather data. Our findings, based on control-function techniques and fixed-effects regressions, reveal that global warming significantly and negatively impacts firms' TFP. Labor productivity declines markedly as temperatures rise, while capital productivity remains unaffected – indicating that TFP is primarily affected through the labor input channel. Sensitivity tests show that firms involved in outdoor activities, such as agriculture and construction, are more adversely impacted. Manufacturing, capital-intensive, and blue-collar-intensive firms also experience significant productivity declines. Geographically, the negative impact is most pronounced in temperate and mediterranean climate areas.
Keywords: D24; J24; Q54; 330; climate change; global warming; firm productivity; Total Factor Productivity (TFP); semiparametric methods to estimate production functions; longitudinal firm-level data